ANALYSIS OF ECONOMIC SHOCKS AFFECTING EURO AREA - MARIUS-CORNELIU MARINAS (Challenges of the Knowledge Society)
The objective of this study is to explain the causes of economic shocks that are manifested in the euro area countries and to examine the possibilities of their adjustment in the context of a common monetary policy. The member countries of the European Monetary Union can not use its own exchange rate or monetary policy to neutralize the economic shocks. Therefore, they must find new ways to adjust the shocks such increase labor market flexibility and promoting reforms in the areas with significant structural rigidities. Common monetary policy also generates asymmetric shocks, as long as Member States are in different phases of the business cycle. In this study I have demonstrated that the ECB's monetary policy has favored Germany and has disadvantaged the countries confronted in present with problems of debt financing.